Insurance Sector: Emerging Distribution Channels - Jampala, Rajesh C. (Indian Journal of Marketing, 2005)
Marketing channels are sets of interdependent organizations involved in the process of making a product or service available for use or consumption1. Organizations have many alternative channels for reaching a market. They can sell directly to the buyers or use one, two or three-level channels. There are basically four Consumer marketing channels. They are zero-level channel, one-level channel, two-level channel, three-level channel. A zero level channel also known as direct-marketing channel consists of a manufacturer selling directly to the final customer. The major examples are door-to-door sales, mail order, telemarketing, Internal marketing etc. In case of one-level channel, it contains one selling intermediary such as a retailer. On the other hand, in a two-level channel, there are two intermediaries. In consumer market, the two level channels is widely prevalent. A three-level channel contains three inter mediaries. Channels normally describe a forward movement of products from source to user.